Physico-Chemical, Functional and Antioxidant Properties of Roe Protein Concentrates from Cyprinus carpio and Epinephelus tauvina - Rao, Galla Narsing (Journal of Food and Pharmaceutical Sciences, 2014)
Roe protein concentrates prepared from Cyprinus carpio (CRPC) and Epinephelus tauvina (ERPC) were investigated for physico-chemical characteristics, functional properties and antioxidant activity. Cyprinus and Epinephelus roes yielded 19.5% and 21.5% of protein concentrates possessing 70.71% and 85.9% protein, respectively. Moisture sorption isotherms of roe protein concentrates indicated the non-hygroscopic nature of CRPC with initial moisture content (IMC) of 8%, which equilibrated at 63% RH and hygroscopic nature of ERPC with IMC of 4.9%, which equilibrated at 42% RH. Water absorption capacity, oil absorption capacity, foam capacity and lower foam stability and emulsifying capacity were found in ERPC than in CRPC respectively. Maximum solubility of protein was 17.79% and 16.89% at pH 12, observed in CRPC and ERPC respectively. Higher buffer capacity was observed in both roe protein concentrates in alkali medium. Antioxidant activity determined by the DPPH radical scavenging activity was higher, and ferric reducing power was observed to be lower in ERPC.